(untitled) (Costos y Gestión, 2023)
In this work we apply the General Theory of Cost, to interpret and map the production process, Marginal Analysis, to analyze the economic suitability of a certain product mix, and Budgeting Techniques, to overlook the future and monetize formulated plans. We set out to promote the development of a proactive attitude in craft-brewed beer small entrepreneurs through a tool designed in a spreadsheet that facilitates the formulation of desired future scenarios whose feasibility can be analyzed from a technical, economic, and financial point of view. It allows the formulation of the sales forecast by business unit, automatically obtaining the sales budget, the production plan, the economic budget and the financial budget, thus enabling a better use of resources. Its correct parameterization is critical, since it will determine the marginal contributions of each style of beer to be manufactured, allowing to learn whether the units to be sold and therefore, the sales revenue, is sufficient to cover both total costs and also make a profit. In order for the tool to be implemented, we have had to simplify certain contents of the cost tools mentioned in the first paragraph, with a lower dose of academic language, to achieve a better understanding by entrepreneurs.